Analisis Blue Ocean Strategy pada PT Cisarua Mountain Dairy Tbk - Dindra Fai’mundiarti Purnamabroto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the application of the Blue Ocean Strategy at PT Cisarua Mountain Dairy Tbk. The Blue Ocean Strategy is a business strategy concept that emphasizes creating uncontested market space and making competition irrelevant. This study analyzes documents related to the business strategies that have been implemented. PT Cisarua Mountain Dairy Tbk is a fast-moving consumer goods (FMCG) company selling packaged protein-based food and beverages in Indonesia, specifically premium yogurt and sausages. The results of the study show that PT Cisarua Mountain Dairy Tbk has implemented several elements of the Blue Ocean Strategy in its efforts to enhance competitive advantage by innovating products, such as ready-to-drink yogurt and premium variants, while eliminating reliance on price promotions and preservatives. This strategy enables Cimory to create new markets, strengthen its position as a leader in healthy foods, and ensure sustainable growth and profitability.